Assimilation of impurities during massive gas injection in ASDEX Upgrade. (20th February 2015) - Pautasso, G.; Mlynek, A.; Bernert, M.; Mank, K.; Herrmann, A.; Dux, R.; Müller, H.W.; Scarabosio, A.; Sertoli, M.
Abstract: Experiments of disruption mitigation with massive gas injection are conducted in ASDEX Upgrade with fast valves located close to the plasma. The valves and the dedicated experiment are described in this paper. The dependence of the fuelling efficiency on plasma and gas parameters is documented and discussed. Several sources of uncertainties affecting its evaluation and physical interpretation have been addressed. An actual fuelling efficiency of 40% has been reached for neon injection with valves close to the plasma and for gas quantities relevant for the thermal and current quench mitigation of ITER. Refuelling the plasma after thermal quench is shown to be feasible; this result opens the possibility of raising the density in a runaway beam and therefore of increasing the collisional drag on and the radiative energy losses of the fast electrons.